Assessing the severity of patch size and perimeter of fragmented forest by using web based spatial analysis - Mohd Noh, Nurfarah Aqilah (2018)
Although forest edges have been studied extensively as an important consequence of fragmentation, a unifying theory of edge influence has yet to be developed. This study intended to take steps toward the implementation of optimal shape of habitat fragments which is circular shape that will be benchmarked against the readily available forest fragments. With online Web-based virtual globes such as Google Earth Pro (GEP), satellite images can be zoomed in the matter of seconds. This study compiled 90 randomly chosen forest fragments around three different regions including Africa, South America and Southeast Asia. Data retrieved from Google Earth Pro will undergo visual interpretation before the digitizing and circular shape were introduced. Landscape parameter including Original Area and Theoretical Area, Original Perimeter, Theoretical Circumference, Latitude and Longitude were taken into consideration to calculate the Fragmentation Effect Value based on the Area [FEVba] and the Fragmentation Effect Value based on Perimeter [FEVbp]. This study answered the question on how Google Earth Pro can be used as a tools at landscape level to measure the severity of forest fragmentation based on the criterion of patch size and perimeter. A statistical analysis using ANOVA was used to assess the [FEVba] and [FEVbp] in the three tropical regions. The results showed that the South America (0.6252 a) have the highest mean for [FEVba] followed by Africa (0.6112 a) and Southeast Asia (0.6026 a). However, mean for [FEVbp] resembled Southeast Asia (0.2202a) as the highest, followed by South America (0.1778a) and Africa (0.1468a). Both Fragmentation Effect Value metrics did not feature significant differences at 5% significant level. This shows that the higher the [FEVba], the bigger the area need to be reserved as more core area can be protected. Despite, the higher the [FEVbp], the more the perimeter that need to be mitigate in order to reduce the edge effects. Fragmentation Effect Value allowed us to gain a better understanding of the current severity of forest fragmentation. In short, this study represents an example of using Fragmentation Effect Value for land cover pattern quantification in three large continents. The severity of forest fragmentation based on the area and perimeter warrants the assumption that the approach developed here is sufficiently generic to be applicable to any forest fragments elsewhere.